The place of the legend of Alexander of Macedon in the larger context of the old Romanian literature = Miejsce legendy Aleksandra Macedońskiego w większym kontekście starej literatury rzymskiej - Ionescu, Dan-Tudor (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The main aim of this quite a short study was to complete the essential image of Alexander of Macedon as he appears through the pages of the Romanian "Alexandria", with an overview on the so-called Old Romanian "popular" literature: somehow the true essence of this hero (Alexander of Macedon) and of his legend had eluded me many times. Compared with the Romanian "History of Troy", so faithful still to Homer and his "epigonoi", the Romanian "Alexandria" seems to the untrained reader of old Romanian literature (like the author of these lines confesses to be) a collection of wild fantasy stories.
Keywords: Alexandria; Alexander of Macedon (356 p.n.e.-323 p.n.e.); Island of the Blessed; Island of Women; Amazons; Cleitarchus; Pseudo-Callisthenes; Nagomudrii; Gates of Paradise; Old Romanian Literature; Aleksandria; Aleksander Wielki (356-323); Wyspy Szczęśliwe; Wyspa Kobiet; Amazonki; Klejtarchos; Pseudo-Kallistenes; Bramy Raju; literatura starorzymska